PENGARUH GOOD GOVERNANCE, SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) PADA OPD KOTA MALANG - AgustiningTyas, Vika Erinna; Tyasari, Irma; Yogivaria, Doni Wirshandono (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2020)
This study aims to examine and explain the effect of good governance, government internal control systems and human resource competencies on the quality of local government financial statements (LKPD) in Malang City Organization (OPD). This quantitative study determined the sample by purposive sampling with the criteria of respondents in 28 OPD Malang in Sub. The Planning and Financial Section is 146 respondents. The type of data used is primary data. Data collection techniques from questionnaires and literature study. The results showed that good governance and the government's internal control system had a significant positive effect on the quality of local government financial reports (LKPD) in Malang City's Organization (OPD). Whereas human resource competency does not significantly influence the quality of the financial statements of the local government (LKPD) in Malang City Regional Organization. The implications of this study can measure what aspects are the priorities of the author in expressing the quality of financial statements in the Government of Malang City